Protein glycosylation during infection by plant pathogenic fungi. Issue 4 (10th February 2021) - Liu, Caiyun; Talbot, Nicholas J.; Chen, Xiao‐Lin
Summary: Glycosylation is a conserved set of post‐translational modifications that exists in all eukaryotic cells. During the last decade, the role of glycosylation in plant pathogenic fungi has received significant attention and considerable progress has been made especially in Ustilago maydis and Magnaporthe oryzae . Here, we review recent advances in our understanding of the role of N‐ glycosylation, O‐ glycosylation and glycosylphosphatidylinositol (GPI) anchors during plant infection by pathogenic fungi. We highlight the roles of these processes in regulatory mechanisms associated with appressorium formation, host penetration, biotrophic growth and immune evasion. We argue that improved knowledge of glycosylation pathways and the impact of these modifications on fungal pathogenesis is overdue and could provide novel strategies for disease control.